2013
DOI: 10.18632/oncotarget.950
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cancer/Testis Antigens is Correlated with Improved Survival in Glioblastoma

Abstract: BackgroundGlioblastoma (GBM) confers a dismal prognosis despite advances in current therapy. Cancer-testis antigens (CTA) comprise families of tumor-associated antigens that are immunogenic in different cancers. The aim of this study was to determine the expression profile of a large number of CTA genes in GBM.MethodsWe selected, from 153 CTA genes, those genes potentially expressed in GBM. The expression pattern of 30 CTA was then evaluated by RT-PCR in a series of 48 GBM and 5 normal brain samples. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 27 publications
(38 reference statements)
1
46
1
Order By: Relevance
“…However, the roles of CTAs in cancer remain ill-defined, and some evidences indicate that they support cancer cell survival, invasion or migration [39], but expression of CTAs has been associated with better outcome in glioblastoma patients [40]. Our results show upregulation of CTAs in xenografts displaying slower growth rates and in three in vitro models undergoing differentiation upon cinacalcet exposure.…”
Section: Discussionmentioning
confidence: 57%
“…However, the roles of CTAs in cancer remain ill-defined, and some evidences indicate that they support cancer cell survival, invasion or migration [39], but expression of CTAs has been associated with better outcome in glioblastoma patients [40]. Our results show upregulation of CTAs in xenografts displaying slower growth rates and in three in vitro models undergoing differentiation upon cinacalcet exposure.…”
Section: Discussionmentioning
confidence: 57%
“…Although most of previous studies have reported an association of CTA expression with poor outcome in multiple myeloma, ovarian, lung, head and neck, and gastric cancers (9,11,21,48,49), Sharma and colleagues (10) described a positive association between expression of CT10 and improved survival for patients with urothelial carcinoma. Along the same line, Freitas and colleagues presented the mRNA positivity of CT antigens as an independent predictor of better OS for patients with glioblastoma (14). Additional prospective studies with independent cohorts of patients with HNSCC are needed to confirm the positive correlation between MAGEA3/6 expression and better disease outcome, but, based on our results, we can speculate that the expression of these CTA in head and neck tumors may have elicited a spontaneous immune response and this could impact favorably the prognosis.…”
Section: Discussionmentioning
confidence: 93%
“…The expression of these antigens has been detected in various types of malignant tumors of different histological types, but rarely in normal somatic tissues, with the exception of immunoprivileged gametogenic tissues. CTAs are described as frequently expressed in melanomas, multiple myeloma, glioblastomas, and carcinomas of the bladder, lung, ovarian, and liver (8)(9)(10)(11)(12)(13)(14). A moderate expression could be detected in breast and prostate tumors (5,15), and they are rarely expressed in renal cell carcinoma, colon cancer, lymphomas, and leukemias (9,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Harnessing CTAs for vaccine or adoptive cell therapy has been done for other diseases, particularly melanoma, although CTAs are expressed in other disease as well, such as glioblastomas, colon, lung, liver, prostate cancer and other tumor types compared to non-malignant somatic cells [41-42]. CTA expression is necessary for these approaches, and our finding of high NY-ESO-1 expression in over 40% of clear cell RCCs suggests that these modalities should be evaluated in NY-ESO-1 expressing RCC.…”
Section: Discussionmentioning
confidence: 99%